The impact of social media on online retail sales - Kumar, Rakesh (Innovative Research Thoughts, 2017)
With their immense influence on consumer behaviour and the way e-commerce is evolving, social media platforms have become formidable forces propelling online retail sales. In this article, we'll take a look at how social media has changed online shopping and what makes it such a powerful sales tool. In this article, we'll go over the ways in which social media sites like Pinterest, Instagram, and Facebook may help online merchants connect with new consumers, improve their brand awareness, and boost sales. Beyond that, we delve into how user-generated content and social media influencers impact consumers' opinions and choices. Additionally, we analyse how social commerce features, such shoppable posts and in-app purchases, simplify the buying process and improve the overall shopping experience. With the help of social media, online stores may reach their target audience, persuade them to buy, and build connections with them that last. The purpose of this paper is to shed light on how social media has affected online shopping and to provide suggestions for stores that want to cash in on this rising trend.